A global analysis of income distribution and capacity utilization interactions: The structuralist view - Tanadej Vechsuruck (The University of Utah, Department of Economics, 2017)
The demand and distributive regimes are estimated from 62 countries around the world based on the Structuralist Goodwin model. The distributive regime appears to be Marxian/profit-squeeze and the demand exhibits a weekly profit-led regime. The profitled demand regime and the profit-squeeze distributive regime are stronger in advanced economies than in emerging economies. The results are also supported when the slopes are allowed to be varied across regions. In the long run, the results reveal that the collective wage suppression would result only in declining wage share, and no positive gain in utilization is found both in developed and developing countries.
Keywords: C23; D3; O11; O47; 330; Panel Analysis; Predator-Prey Models; Distributive-Demand Dynamics; Globalization